Laparoscopy-assisted versus enteroscopy-assisted endoscopic retrograde cholangiopancreatography (ERCP) in Roux-en-Y gastric bypass: a meta-analysis - Ayoub, Fares; Brar, Tony S.; Banerjee, Debdeep; Abbas, Ali M.; Wang, Yu; Yang, Dennis; Draganov, Peter V. (Endoscopy International Open, 2020)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is technically challenging in patients with Roux-en-Y gastric bypass (RYGB) anatomy, which is increasing in frequency given the rise of obesity. Laparoscopy-assisted ERCP (LA-ERCP) and enteroscopy-assisted ERCP (EA-ERCP) are distinct approaches with their respective strengths and weaknesses. We conducted a meta-analysis comparing the procedural time, rates of success and adverse events of each method.Patients and methods A search of PubMed, EMBASE and the Cochrane library was performed from inception to October 2018 for studies reporting outcomes of LA or EA-ERCP in patients with RYGB anatomy. Studies using single, double, ‘short’ double-balloon or spiral enteroscopy were included in the EA-ERCP arm. Outcomes of interest included procedural time, papilla identification, papilla cannulation, therapeutic success and adverse events. Therapeutic success was defined as successful completion of the originally intended diagnostic or therapeutic indication for ERCP. Results A total of 3859 studies were initially identified using our search strategy, of which 26 studies met the inclusion criteria. The pooled rate of therapeutic success was significantly higher in LA-ERCP (97.9 %; 95 % CI: 96.7–98.7 %) with little heterogeneity (I2 = 0.0 %) when compared to EA-ERCP (73.2 %; 95 % CI: 62.5–82.6 %) with significant heterogeneity (I2: 80.2 %). Conversely, the pooled rate of adverse events was significantly higher in LA-ERCP (19.0 %; 95 % CI: 12.6–26.4 %) when compared to EA-ERCP (6.5 %; 95% CI: 3.9–9.6 %). The pooled mean procedure time for LA-ERCP was 158.4 minutes (SD ± 20) which was also higher than the mean pooled procedure time for EA-ERCP at 100.5 minutes (SD ± 19.2).Conclusions LA-ERCP is significantly more effective than EA-ERCP in patients with RYGB but is associated with a higher rate of adverse events and longer procedural time.